2012
DOI: 10.1111/j.1095-8339.2012.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Good Heavens what insect can suck it’- Charles Darwin, Angraecum sesquipedale and Xanthopan morganii praedicta

Abstract: In this review we provide a detailed description of Darwin's prediction of the coevolution of a long-spurred orchid, Angraecum sesquipedale, and a long-tongued moth, his correspondence on the subject, the history of the moth and the subsequent literature. On seeing the long spur of A. sesquipedale, Darwin predicted that its pollinator would be a moth with a long proboscis. For more than a century following Darwin's prediction this was assumed to be the case. The pollinator was taken to be Xanthopan morganii pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 61 publications
0
54
0
5
Order By: Relevance
“…Selection pressures exerted by diverse floral structure (Soltis et al, ; Tiple et al, ) probably have resulted in the diversity of proboscis structure among flower visitors. The best‐known relationship between flower and proboscis structure is the corresponding length of the floral tube and the proboscis (Kunte, ; Krenn, ; Arditti et al, ; Bauder et al, ); however, other patterns can be found. The Papilionidae and Nymphalidae, for example, which feed on nectar from similar (e.g., larger) flowers (Tiple et al, ), have similar dorsal legular shapes that differ from those of pierids.…”
Section: Discussionmentioning
confidence: 99%
“…Selection pressures exerted by diverse floral structure (Soltis et al, ; Tiple et al, ) probably have resulted in the diversity of proboscis structure among flower visitors. The best‐known relationship between flower and proboscis structure is the corresponding length of the floral tube and the proboscis (Kunte, ; Krenn, ; Arditti et al, ; Bauder et al, ); however, other patterns can be found. The Papilionidae and Nymphalidae, for example, which feed on nectar from similar (e.g., larger) flowers (Tiple et al, ), have similar dorsal legular shapes that differ from those of pierids.…”
Section: Discussionmentioning
confidence: 99%
“…; Arditti et al . ). However, diffuse community level rather than paired co‐evolutionary processes are supposed to drive the evolution of proboscis and flower lengths, because one‐to‐one interactions are rare in plant–pollinator systems and, when multiple species interact, selection pressures imposed by one species are not independent of the selection pressures imposed by a second species (Nilsson et al .…”
Section: Introductionmentioning
confidence: 97%
“…Pollination systems are often thought of as prime examples of co‐evolution, and there are many classic examples of tight specialization and specific co‐evolution in pollination systems: for example, Darwin's sphinx moth (Arditti, Elliott, Kitching, & Wasserthal, ; Darwin, ), or figs and fig wasps (Cruaud et al., ). Most pollination systems, however, do not exhibit the specialization found in host–parasite interactions and tight interactions are the exception rather than the rule (Waser, Chittka, Price, Williams, & Ollerton, ).…”
Section: Introductionmentioning
confidence: 99%